Interaction between “dissipative solitons” stabilized by aggregation in excitable kinetics - Mangioni, Sergio Enrique (2014)
We consider that a population of individuals governed by the Nagumo model is characterized by predisposition towards aggregation. “Dissipative solitons” interacting are solutions for such system. We changed the possibility of extinction, predicted by Nagumo model, by a uniform background of low population’s density and then we observed relevant effect on interaction between “solitons”.